Erforschung und wirtschaftliche Erschließung der Krillbestände und Nutzfische in der Antarktis: Bericht über die Antarktis - Expedition 1975/76 der Bundesrepublik Deutschland - Sahrhage, Dietrich; Schreiber, Wolfgang; Steinberg, Rolf; Hempel, Gotthilf (Bundesforschungsanstalt für Fischerei Hamburg, 1977)
From mid November 1975 till mid May 1976 an integrated research programme has been carried out in the Atlantic sector of the Antarctic between 68°West and 14°East and 50° and 60°South by means of the FRV "Walther Herwig" and FMS "Weser". Data on krill and krill larvae have been gathered concerning frequency, horizontal and vertical distribution with respect to the krill biology. Furthermore hydrographical data on the environmental conditions have been recorded. The problems of locating and catching the krill have been solved to a large extent. The processing of krill and the development of krill products has been tested bt a great number of different technologies. The investigations have been concentrated on the developaent of the products for human consumption. Besides krill, antarctic fishes have been caught, investigated and partly processed.